Projeto Lopes Rodrigues: continuidades e rupturas nas conexões entre ensino psiquiátrico e prática assistencial em Minas Gerais (1920-1930) - Renato Diniz Silveira (2008)
The teaching of psychiatry in the context of early twentieth century Brazil is examined, through a case study of the Faculty of Medicine of the University of Minas Gerais, in the period between 1920 and 1930. The conditions for sustaining a medical school linked to theories and practices of psychiatric care are analysed, focusing on the project undertaken by Hermelino Lopes Rodrigues (1898-1971), professor of psychiatry in Belo Horizonte. The Lopes Rodrigues Project, initiated in 1929, was designed with the purpose of connecting the teaching position at the Faculty of Medicine with the practices of assistance to the mentally ill used at Institute Raul Soares. In this public hospital, individuals who presented mental disorders and / or anti-social behaviours were hospitalized and previously subjected to inhuman treatments, including the use of physical violence against patients. With the purpose of understanding the actions of Lopes Rodrigues aimed at the humanization of these treatments, and the relationships between these actions and the history of psychiatry and of scientific teaching, the theoretical and methodological approaches proposed by Bruno Latour for the analysis of the history of science were used. From Latours point of view, scientific activity is better understood when analyzed in its relations with the social and cultural context through the metaphor of a circulatory system. In this system, five circuits are considered to examine integrated scientific studies: mobilization of the world, autonomization, alliances, public representation, and links or knots. The use made by Lopes Rodrigues of psychiatric theories originated in Europe and disseminated in Brazil through the work of Juliano Moreira at Hospício Nacional in Rio de Janeiro was analyzed from the standpoint of the concept of appropriation developed by Roger Chartier. This author shows that, in the process of transmission, knowledge is not passively acquired by the receiver. On the contrary, the person performs a work of transformation on the knowledge received. We examined various sources for the research, such as newspapers of the time, scientific journals, magazines, in addition to educational documents such as minutes of meetings or materials provided by the daily life of the Faculty of Medicine of the University of Minas Gerais. The crossing of these various sources showed that Lopes Rodrigues Project did not succeed in including psychiatric education in the dynamics of the relationship between theoretical knowledge and practical assistance to the mentally ill. Stemming from Bruno Latours emphasis on the need to strengthen various connections to provide support for a scientific project, and from the historical evidence provided by this case study, it is concluded that the link between theoretical perspectives and practical assistance within the medical school is essential for the of training the psychiatrist. Also, in relation to Project Lopes Rodrigues, it is concluded that its creator could not perform connections and joints necessary for the support of his project, mainly because he did not include important dimensions identified by the methodology of Bruno Latour in scientific studies.